2010
DOI: 10.1007/s12032-010-9694-x
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 expression and triple negative profile in breast carcinoma

Abstract: Many biomarkers for breast cancer prognosis have been proposed during the last two decades, among which HER2 and oestrogen receptors are of common use in routine clinical practice. However, in recent years, BCL2 has been recognized as an important prognostic parameter in human breast cancer, although its clinical utility is well established. The aim of this study was to examine the protein expression patterns of BCL2, HER2, oestrogen (ER) and progesterone receptors (PR) and to evaluate their correlation with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
(42 reference statements)
4
24
1
Order By: Relevance
“…To our knowledge, this is the first study to document that Bcl-2 positivity has directionally opposite effects on survival in TN and non-TN tumors. Of note, this finding is inconsistent with a previously published report that showed Bcl-2 expression was associated with improved survival in 84 Tunisian patients with TN tumors [5]. These discrepancies may be due to our use of more specific criteria in determination of TN status.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…To our knowledge, this is the first study to document that Bcl-2 positivity has directionally opposite effects on survival in TN and non-TN tumors. Of note, this finding is inconsistent with a previously published report that showed Bcl-2 expression was associated with improved survival in 84 Tunisian patients with TN tumors [5]. These discrepancies may be due to our use of more specific criteria in determination of TN status.…”
Section: Discussioncontrasting
confidence: 88%
“…To our knowledge, the few studies exploring the Bcl-2 expression in TN breast cancer have reported findings consistent with the literature on other molecular tumor types-namely, Bcl-2 positivity is associated with improved survival rates [4,5,20]. Many of these studies, however, were limited by low n values of patients with TN breast cancer.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is not surprising because a recent study proved that Bcl-2 is a prognostic factor in women with both ER positive and ER negative disease and also in women with both Her2 negative and Her2 positive disease and its positivity is maintained across various molecular subtypes of breast cancer (Dawson et al, 2010). Although the frequency of Bcl-2 expression ranged from 69-73% in previous studies (Dawson et al, 2010;Kallel-Bayoudh et al, 2011), a controversy exists because they found that TNBC tend commonly to have lower Bcl-2 expression compared to non-TNBC (Tawfik et al, 2010;de Ruijter et al, 2011), moreover, Bcl-2 oncogene expression was found to be statistically greater in the ER positive breast tumors compared to ER negative tumors (dos Santos et al, 2008). Such discrepancies between the studies are likely to be due to the wide variation between the methodologies and types of cases studied (Cecka et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…It was previously reported that GATA-3 functions as a critical regulator of commitment and maturation of cancer cells in the luminal A epithelial lineage, i.e., the expression of GATA-3 regulates luminal differentiation (37). The anti-apoptotic marker Bcl-2 has been proven to be an independent molecular signature, alone or in combination with Ki-67 as a marker pair, in the luminal type of breast cancer (38)(39)(40)(41)(42).…”
Section: Luminalmentioning
confidence: 99%